Pattern of Use of Biosimilar and Originator Somatropin in Italy: A Population-Based Multiple Databases Study During the Years 2009–2014 - Marcianò, Ilaria; Ingrasciotta, Ylenia; Giorgianni, Francesco; Ientile, Valentina; Chinellato, Alessandro; Tari, Daniele Ugo; Gini, Rosa; Cannavò, Salvatore; Pastorello, Maurizio; Scondotto, Salvatore; Cananzi, Pasquale; Traversa, Giuseppe; et al. (Frontiers in Endocrinology, 2018)
Purpose Somatropin (rGH) is approved in children and adults for several conditions involving growth disturbances and the corresponding biosimilar is available in Italy since 2006. No population-based data are available on the pattern of rGH use in Italian clinical practice. This study aimed at exploring the pattern of biosimilar and originator rGH use in six Italian centres, where different policy interventions promoted biosimilar use. Methods This population-based, drug-utilization study was conducted in the years 2009-2014, using administrative databases of Umbria, Tuscany, and Lazio Regions and Local Health Units of Caserta, Treviso and Palermo. Naïve rGH users were characterized, and prevalence of use and discontinuation were assessed over time. Results Among 6,785 patients treated with rGH during the study years, 4,493 (66.2%) were naïve users (males/females= 1.3), mostly affected by GH deficiency. The prevalence of rGH use increased from 2009 to 2010, remaining stable thereafter, but it was heterogeneous across centers (2-fold higher prevalence of use in centre n.2 than centres n.4 and 1 in 2014). Biosimilar rGH uptake increased over time but was low (7.8% in 2014) and heterogeneous as well. Discontinuation of rGH therapy occurred in 54.0% of naïve users, more frequently in females than males (58.1% vs. 50.9%). During the first year of treatment, discontinuation was frequent (39.9%), but no statistically significant differences were observed in treatment persistence for biosimilar vs. originator rGH (p> 0.05). Conclusions Geographical heterogeneity in the prevalence of rGH use was observed. Similarly, the biosimilar rGH uptake was low and variable across centres. Post-marketing monitoring is required to continuosly monitor the benefit-risk profile of rGH, thus guaranteeing greater savings than only promoting lowest cost rGH.